Prospect Mapping of Kerry Field, Taranaki Basin - Harolanuar, Nurul Ain (2016)
The study was commissioned to explore new potential reservoir within Farewell Formation by integrating well log and seismic data. The study is focused in Kerry Field which located at the southern area of Taranaki Basin, New Zealand. 3D seismic interpretation and well log analysis were done to evaluate hydrocarbon potentials of the reservoir using Petrel 2014.